PENGARUH BELANJA RUTIN DAN BELANJA MODAL PADA KINERJA KEUANGAN PEMERINTAH - Yulia Astiti, Desak Nyoman; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
One of the elements that is related to the measurement of financial performance of local governments are expenses areas. Nowadays, the effectiveness of allocation in regional spending tend to be low. This study aims to determine the effect of Routine Expenditure and Capital Expenditure on Local Governments' Financial Performance. The study was conducted in Bali Province with the scope of the eight regencies and one city in the period of five years, from 2009-2013. The resource of this research was the secondary data from the Bureau of Finance in Bali Province. The hypothesis was tested with PLS. Based on the analysis, routine expenditure does not affect the financial performance of local governments and capital expenditures can affect the financial performance of local governments. The independence variable, routine expenditure and capital expenditure can affect the financial performance of local governments by 22.3%, while the remaining 77.7% is influenced by other variables.
Keywords: routine expenditure, capital expenditure, the financial performance of local governments